Influence of hydrothermal synthesis parameters on the properties of hydroxyapatite nanoparticles - Kuśnieruk, Sylwia; Wojnarowicz, Jacek; Chodara, Agnieszka; Chudoba, Tadeusz; Gierlotka, Stanislaw; Lojkowski, Witold (Beilstein Journal of Nanotechnology, 2016)
Hydroxyapatite (HAp) nanoparticles of tunable diameter were obtained by the precipitation method at room temperature and by microwave hydrothermal synthesis (MHS). The following parameters of the obtained nanostructured HAp were determined: pycnometric density, specific surface area, phase purity, lattice parameters, particle size, particle size distribution, water content, and structure. HAp nanoparticle morphology and structure were determined using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). X-ray diffraction measurements confirmed crystalline HAp was synthesized, which was pure in terms of phase. It was shown that by changing the synthesis parameters, the diameter of HAp nanoparticles could be controlled. The average diameter of the HAp nanoparticles was determined by Scherrer’s equation via the Nanopowder XRD Processor Demo web application, which interprets the results of specific surface area and TEM measurements using the dark-field technique. The obtained nanoparticles with average particle diameter ranging from 8–39 nm were characterized by having homogeneous morphology with a needle shape and a narrow particle size distribution. Strong similarities were found when comparing the properties of some types of nanostructured hydroxyapatite with natural occurring apatite found in animal bones and teeth.
Keywords: hydroxyapatite; microwave hydrothermal synthesis; nanoparticle size control; physical properties of HAp NPs; room temperature synthesis